Finance and fake news - Aaron Sahr (Finance and Society, 2021)
Vogl interprets the structural discrediting of knowledge and the corresponding glorification of mere assertion as nothing less than the tectonics of our time. But this diagnosis presupposes that it makes sense to examine different fields in terms of their epistemology - and to measure them against the same standards.
Keywords: 300